TV exposure and study habits of UPV High School students - Brasileño, Hazel Alice P.
This study was conducted to find out the level of television exposure of high school students, to know their study habits and to find out the relationship between TV exposure and the study habits of UPV high school students., A study was conducted among UP Visayas High School students where a total of 137 respondents from first, second, third and fourth year levels provided the major data of the study. A three-paged questionnaire was the instrument used in gathering data. It included: respondents's level of exposure to TV and the student's study habits. The last part related TV exposure with study habits. Findings revealed that there is 99 television viewership which means that there is a high level of TV exposure among respondents. Number of hours of viewing ranges from 30 minutes to a maximum of six hours. Most of the programs watched were foreign canned shows and were entertainment in nature. Preferred viewing schedule of most students is 7-9 p.m. Findings also showed that most (54) of the parents imposed restrictions on their children's viewing particularly on the number of hours students watched TV. On the other hand, ninety-six percent (96) of the students studied their lessons. For those who studied majority do so everyday for a minimum of 30 minutes and a maximum three hours. Students preferred to study between 8-10 p.m. three hours. Students preferred to study between 8-10 p.m. Students study mainly to attain high grades. In relating TV exposure and study habits results showed that TV viewing consumes most of the free time of students and that time alotted for study is utilized for viewing the medium. However TV viewing is also helpful to the students in that it gives them information and ideas which they applied to their lessons. The chi square test for independence was used to find out if there is a relationship between the two variables TV exposure and study habits. Results showed that there is a relationship between TV exposure and study habits, that is the more exposed the students are to TV the greater is the probabilit that the number of time spent for studying will be lessened.